The Weave: A Suburban Work - Bruce A. Johnson (Oz, 1996)
As first a spectator, the architect is always already an agent at work in the creation of the difference of which Duchamp speaks. This occurs through the simple misreading of an idea-philosophy offered forth for contemplation.